Mastering Clojure Data Analysis. - Rochester, Eric (Community experience distilled., 2014)
This book consists of a practical, example-oriented approach that aims to help you learn how to use Clojure for data analysis quickly and efficiently. This book is great for those who have experience with Clojure and who need to use it to perform data analysis. This book will also be hugely beneficial for readers with basic experience in data analysis and statistics.